KOMUNIKASI INTERPERSONAL Pengaruh Komunikasi Interpersonal Dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Wild Original Majalengka - Istiono, Deni; Kurniasih, Nining; Pamungkas, Pupung (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2025)
In the business world, business actors must be able to maintain their existence and compete with other companies. To achieve this goal, a high level of customer satisfaction is required. Interpersonal Communication and Service Quality are factors that can increase customer satisfaction. This study aims to determine how the influence of Interpersonal Communication and Service Quality on Consumer Satisfaction at Wild Original Majalengka. This research is a survey research type using a descriptive and verification approach. The population in this study is the Wild Original Majalengka consumers with a total sample of 100 respondents. The sampling technique used is Nonprobability Sampling. The data collection technique in this study was a questionnaire using a Likert scale. Data analysis using classical assumption test, multiple regression analysis, coefficient of determination, model feasibility test and partial hypothesis testing. The results of hypothesis testing indicate that Interpersonal Communication has a positive and significant effect on Consumer Satisfaction. Service quality has a positive and significant effect on consumer satisfaction